Does size of the cochlear nerve affect postoperative auditory performance in pediatric cochlear implant patients with normal cochlear nerves? - Gozen,Emine Deniz (2022)
Abstract Introduction Cochlear implantation is an effective treatment method for severe to profound hearing loss. Many factors that may influence cochlear implantation success have been explained in previous studies. Apart from those, minor differences in size of normal cochlear nerves may affect postoperative performance. Objective To investigate whether the minor differences in cochlear nerve size in normal cochlear nerves affect postoperative cochlear implant performance. Methods 30 pediatric prelingually deaf patients who were treated with cochlear implantation were included in this study. From the reconstructed parasagittal magnetic resonance images, the diameter and cross-sectional area of the cochlear nerve on the ipsilateral and contralateral side were measured. Auditory evaluations were performed 1, 3, 6 and 12 months following the first fitting. All the analysis was performed by using EARS®, evaluation of auditory responses to speech tool. Correlation between cochlear nerve diameter, cross-sectional area and postoperative auditory perception was analyzed to determine whether variation in cochlear nerve size contributes to postoperative auditory performance. Results The mean diameter of the cochlear nerve on the ipsilateral side was 718.4 μm (504.5 − 904.3 μm) and mean cross sectional area was 0.015 cm2 (0.012 − 0.018 cm2). On the contralateral side the mean cochlear nerve diameter was 714.4 μm (502.6 − 951.4 μm) and mean cross sectional area was 0.014 cm2 (0.011 − 0.019 cm2). The correlation between the diameter and cross-sectional area of the ipsilateral and contralateral cochlear nerve revealed no significance. Mean score at first month monosyllable-trochee-polysyllable test, MTP1, was 0.17 (0.08 − 0.33), at 6th month with 6 words test, 6th month MTP6 was 0.72 (0.39 − 1.0), at 6th month with 12 words, 6th month MTP 12 was 0.46 (0.17 − 0.75) and at 12th month with 12 words, 12th month MTP12 was 0.73 (0.25 − 1.0). There was no correlation between the monosyllable-trochee-polysyllable test, values at any time with the diameter of the ipsilateral cochlear nerve. However, the first month MTP, 6th month MTP6 and 12th month MTP12 correlated with the cross-sectional area of the ipsilateral cochlear nerve. Conclusion Measuring the cross sectional area of the normal- appearing cochlear nerve may give important prognostic knowledge on cochlear implant outcomes. In patients with a larger cross sectional area the auditory performance was better and faster. Although normal appearing, slight differences on cross sectional area of the cochlear nerve may affect performance. Measuring the size of the cochlear nerve on parasagittal magnetic resonance images may provide beneficial information on the postoperative rehabilitation process.